Bone Marrow Stem Cells‐Seeded Polyethylene Terephthalate Scaffold in Repair and Regeneration of Rabbit Achilles Tendon. Issue 11 (7th October 2018) - Cai, Jiangyu; Yang, Yimeng; Ai, Chengchong; Jin, Wenhe; Sheng, Dandan; Chen, Jun; Chen, Shiyi
Abstract: The objective of this study was to evaluate the effect of bone marrow stem cells (BMSCs)‐seeded polyethylene terephthalate (PET) scaffold for Achilles tendon repair in a rabbit model. The allogeneic BMSCs were seeded onto the PET scaffold and cultured in vitro for 14 days. Sixteen mature New Zealand rabbits underwent surgery to establish a 2‐cm Achilles tendon defect model. The BMSCs‐seeded PET scaffold was implanted into the defect of one limb (BMSCs‐PET group), while the PET scaffold without BMSCs was implanted into the defect of contralateral limb as the control (PET group). All rabbits were sacrificed at 6 and 12 weeks after surgery. At 12 weeks after surgery, macroscopic and histological results showed formation of tendon‐like tissues, and the structure was more mature in the BMSCs‐PET group. Immunohistochemical analysis and real‐time polymerase chain reaction (RT‐PCR) demonstrated that the collagen I and collagen III were significantly higher in the BMSCs‐PET group compared with those in the PET group. Mechanically, both the failure load and the average stiffness were significantly higher in the BMSCs‐PET group than those in the PET group. In conclusion, BMSCs‐seeded PET scaffold could effectively facilitate the healing process after being implanted in a rabbit Achilles tendon defect model.